207 Laparoscopic versus Open Surgery for Locally Advanced Colon Cancer: A Retrospective Cohort Study. (4th May 2021) - Tay, P W L; Xiao, J L; Lim, W H; Wong, N W; Chong, C S
Abstract: Introduction: While an increasing number of studies substantiate the non-inferiority of laparoscopy to open surgery for pT4 colon cancer, studies investigating its value specific to the subgroup pT4a in right hemicolectomies remain scarce. Method: We performed a retrospective cohort analysis in National University Hospital of Singapore of patients who underwent a right hemicolectomy for pT4 colon cancer. Statistical analysis was performed using Wilcoxon rank sum test and chi square/fisher exact. Results: In total, 65 patients had T4 colon cancer. 55 underwent right hemicolectomy and 10 underwent extended right hemicolectomy. Baseline demographics were similar in laparoscopic (n = 27) and open (n = 38) groups, with no significant difference in proportion of pT4a patients (p = 0.724). For pT4, 30-day mortality (7%, 5% respectively, p = 0.723), overall survival (p = 0.1903) and disease-free survival (p = 0.3476) did not differ significantly between laparoscopic and open groups. R0 resection rates were significantly higher in laparoscopic group (p = 0.039). pT4a subgroup analysis found similar observations. Other complications including postoperative wound infection and anastomotic bleed were not significantly different for both T4 and T4a analysis. Conclusions: This study presented comparable safety and oncological outcomes between the two surgical methods for right hemicolectomy, suggesting laparoscopy to be a viable alternative approach for locally advanced right colon cancer.